The accuracy of 18F-Fluorodeoxyglucose positron emission tomography/computed tomography in the evaluation of bone lesions of undetermined origin - Cuneyt Tamam; Muge Tamam; Mehmet Mulazimoglu (World Journal of Nuclear Medicine)
The aim of the current study was to determine the diagnostic accuracy of whole-body fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) in detecting carcinoma of unknown primary (CUP) with bone metastases. We evaluated 87 patients who were referred to FDG-PET/CT imaging and reported to have skeletal lesions with suspicion of malignancy. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were calculated. The median survival rate was measured to evaluate the prognostic value of the FDG-PET/CT findings. In the search for a primary, FDG-PET/CT findings correctly diagnosed lesions as the site of the primary true positive (TP) in 64 (73%) cases, 4 (5%) findings diagnosed no site of a primary, and none were subsequently proven to be true negative (TN); 14 (16%) diagnoses were false positive (FP) and 5 (6%) diagnoses were false negative (FN). Life expectancy was between 2 months and 25 months. Whole-body FDG-PET/CT imaging may be a useful method in assessing the bone lesions with suspicion of bone metastases.